Techno-Economic Evaluation of Renewable-Material Construction for Low-Income Housing Communities - Daniel Obokhai Uduokhai; Baalah Matthew Patrick Garba; Mike Ikemefuna Nwafor; Adepeju Nafisat Sanusi (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
The growing demand for affordable and climate-resilient housing in low-income communities across the Global South has intensified the need for innovative construction approaches that balance cost efficiency, environmental responsibility, and social welfare. This study presents a techno-economic evaluation of renewable-material construction systems—such as compressed stabilized earth blocks (CSEB), bamboo composites, recycled aggregates, and bio-based insulation—applied to low-income housing development. It investigates the performance, lifecycle costs, structural safety, and sustainability benefits of renewable materials relative to conventional concrete-based construction. Findings demonstrate that renewable-material technologies can reduce embodied energy, carbon emissions, and long-term maintenance costs, while enabling localized production and job creation within community-based supply chains. The analysis also highlights affordability advantages derived from reduced transportation requirements, modular prefabrication, and adaptive design approaches tailored to local climatic conditions. Despite these advantages, several techno-economic barriers persist, including limited industrial scaling, lack of standardized testing and certification, skill gaps in implementation, and market skepticism regarding durability and performance. The study emphasizes the importance of supportive policies—such as green building codes, tax incentives, and microfinance innovations—to enhance market competitiveness and drive broader adoption. A multi-criteria evaluation framework is proposed to guide decision-makers in assessing material choices across technical, economic, and socio-environmental dimensions. Ultimately, renewable-material construction provides a viable pathway to expand safe, sustainable, and dignified housing access for low-income populations while contributing to national climate goals and circular economy strategies. Strengthening research, capacity building, and public-private partnerships will be essential to accelerating this transition and unlocking widespread socio-economic benefits.